2005
DOI: 10.1523/jneurosci.3984-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin Modulates Neural Circuitry for Social Cognition and Fear in Humans

Abstract: In non-human mammals, the neuropeptide oxytocin is a key mediator of complex emotional and social behaviors, including attachment, social recognition, and aggression. Oxytocin reduces anxiety and impacts on fear conditioning and extinction. Recently, oxytocin administration in humans was shown to increase trust, suggesting involvement of the amygdala, a central component of the neurocircuitry of fear and social cognition that has been linked to trust and highly expresses oxytocin receptors in many mammals. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

74
981
10
35

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,430 publications
(1,126 citation statements)
references
References 40 publications
74
981
10
35
Order By: Relevance
“…44 In that study, the authors found activation of the left amygdala in patients with contamination fear and washing behaviors, possibly linking clinical data with our experimental results. Kirsch et al 81 showed that intranasal OT reduced amygdala activation in healthy subjects submitted to fear-inducing visual stimuli, supporting that OT release in the CeA participate in a fearreduction mechanism. As some regions of prefrontal cortex (PFC) are strongly related to OCD (e.g., right superior and dorsolateral regions of PFC), 44,82 a possible circuitry of anxiety-related symptoms in OCD patients (without tics) suggest a failure of inhibitory properties of projections from PFC to amygdala 44 and, additionally, a possible failure of OT receptors to respond to OT activation.…”
Section: Discussionmentioning
confidence: 98%
“…44 In that study, the authors found activation of the left amygdala in patients with contamination fear and washing behaviors, possibly linking clinical data with our experimental results. Kirsch et al 81 showed that intranasal OT reduced amygdala activation in healthy subjects submitted to fear-inducing visual stimuli, supporting that OT release in the CeA participate in a fearreduction mechanism. As some regions of prefrontal cortex (PFC) are strongly related to OCD (e.g., right superior and dorsolateral regions of PFC), 44,82 a possible circuitry of anxiety-related symptoms in OCD patients (without tics) suggest a failure of inhibitory properties of projections from PFC to amygdala 44 and, additionally, a possible failure of OT receptors to respond to OT activation.…”
Section: Discussionmentioning
confidence: 98%
“…Involvement of the ventral striatum, which is part of the reward-related dopaminergic nigrostriatal system, suggests that pictures of one’s own child may have a higher “incentive value” for securely attached mothers and hence facilitate maternal responsiveness and approach behaviors (Strathearn et al, 2009). On the other hand, adult women with an insecure attachment representation show increased activation of the amygdala in response to baby cries (Riem et al, 2012) and heightened amygdala reactivity may partly stem from insufficient OT signaling (Kirsch et al, 2005). One may speculate that mothers with an insecure attachment style, which can be a result of problematic parental care experiences in the mother’s own childhood, are more prone to perceive infant distress as aversive, which can lead to frustration or even abusive behavior towards the child (Reijneveld et al, 2004).…”
Section: Ot and Early-life Stress (Els) – Role In Shaping Neural Cmentioning
confidence: 99%
“…Given the expression of OTRs within key stress-regulatory regions (e.g., amygdala, PVN), stress-buffering effects of OT (Cardoso et al, 2014; Heinrichs et al, 2003), and OT-induced downregulation of amygdala reactivity (Kirsch et al, 2005), OT might serve a protective role against the development of stress-related disorders such as MDD or PPD. In a recent meta-analysis, OT was shown to not attenuate HPA axis reactivity after stress induction per se but does so after laboratory stress protocols that robustly activate the HPA axis (Cardoso et al, 2014).…”
Section: Ot and Early-life Stress (Els) – Role In Shaping Neural Cmentioning
confidence: 99%
“…Since oxytocin is also considered as a key mediator of social cognition in humans [37] and this effect has been postulated to specifically involve the OT system in the Amy [38], the OTR upregulation observed here might also be associated with a possible nicotine regulation of cognition through an OTR-dependent mechanism. However, this hypothesis needs to be further investigated.…”
Section: Discussionmentioning
confidence: 71%